NATURAL DIET OF PENAIED PRAWNS IN THE COASTAL WATERS OF MUMBAI - Deshmukh, V. D.; Sawant, M. S.; Mane, S. J.; Hule, A. S. (Journal of Indian Fisheries Association, 2006)
Foregut contents of eight commercially important species of penaeidprawns namely Penaeus merguiensis, Metapenaeus affinis, M. monoceros, M. brevicornis, Parapenaeopsis stylifera, P. lwrdwickii, P. ,r,'culptilis and Solenocera crassicornis were investigated from inshore, nearshore and offshore fishing grounds ofMumbai. Feeding intensity and index of preponderance (IP) of the dietary items were compared statistically for the species, sexes, fishing areas and maturity condition of females. AU the species except M. monoceros and P. sculptilis showed that females were better fed than males. The feeding intensity in the three depth-zones was different for M. affinis, M. brevicornis, M. monoceros, P. hardwickii and S. crassicornis, and un.iform for P. merguiensis, P.stylifera and P. sculptilis. Acetes spp., prawn remains, polychaetes, benthic crustaceans, foraminifers and fish remains were the important food items of the prawns. Dietary comparison between the two sexes of the species did not show any difference, but mature females of M. monoceros and P. sculptilis had different diets. Comparison of food items for all the species together showed significant difference between the three areas. Crustacean diet was the favourite in the inshore and nearshore, and polychaetes in the offshore waters. All the species except P. hardwickii showed difference in their dietary composition in the three depth-zones. It is concluded that these coexisting species are primarily carnivorous and exhibit diverse food preferences in different depth-zones by browsing on interstitial organisms, chasing epipelagic prey, raptorial predation, scavenging on dead organisms or adopting different temporal abundance to avoid inter-specific competition for food.Keywords: Foregut, penaeid prawns, diet inter-specificity